Experimental Study of Forest Fuel Ignition by the Source of Limited Energy Capacity; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Baranovskiy N. V. Nikolay Viktorovich (Modelling and Numerical Simulation, Algorithms and Mathematical Methods for Applied Problems, 2015)
Title screen